STRATEGI KEUNGGULAN BERSAING PERUSAHAAN MELALUI LOYALITAS PELANGGAN PADA PT TUNAS BATAM KARYA - Hendri` Herman (LPPM Universitas Putera Batam, 2018)
This study aims to see the influence of customer loyalty to competitive advantage strategy. The object of this research is PT Tunas Batam Karya with the respondents are the customers. The number of population in this study as many as 11. Samples determined by using saturated samples in which the entire population in this study used as a sample. From the results of the study found that customer loyalty has a significant influence on competitive advantage strategy. Therefore, it is necessary for the company to pay attention to customer loyalty.